Biosynthesis of organic molecules via artificial cascade reactions based on cytochrome P450 monooxygenases - Ren-Jie Li; Zhongwei Zhang; Carlos G. Acevedo-Rocha; Jing Zhao; Aitao Li (Green Synthesis and Catalysis, 2020)
Cytochrome P450 monooxygenases (P450s) play crucial roles in the oxyfunctionalization of non-activated hydrocarbons, thus bridging the gap between simple molecules and high value-added fine chemicals. The introduction of P450s into artificially designed cascade reactions provides an exciting opportunity to accomplish challenging reactions and access organic compounds that cannot be achieved by traditional chemical catalysts or by natural metabolic pathways. The main objective of this review is to provide an overview of different types of artificially designed multi-step cascades in which P450s are involved as key catalysts in the biosynthesis of various organic molecules. The different efforts include in vitro multi-enzymatic biocatalytic cascades, in vivo biocatalytic cascades as well as chemo-enzymatic hybrid cascades. Overall, this work provides an overview of cascade reactions involving P450s with various potential applications for the industrial production of food, cosmetics, polymers and pharmaceuticals.